An analysis on the uses of data modeling in database application development / Hafiza Ahmad - Ahmad, Hafiza (2004)
Database applications development can be part of a larger project as it's become increasingly complex each day. It's providing the basis not only for business applications, but also for searching new market opportunities in this era of competitive global marketplace. Thus, it is important to model, design and maintain this complex database. From the survey that being made to the most of the system developers, it being found that data modeling approach can absolutely assist in ensuring the accuracy and the consistency of the data required by this database. It being found that by using data modeling approach, all the data that being required for the development will be correctly and completely identified. The survey also shows that most of the respondents used the relational model and the Entity Relationship Approach as its tool to model their data. There are also the indications from the Chisquare test of associations where the successful complete data model is dependent on educational level and development times. As there is an evolution in the data modeling approach, the developer may decide on which approach they may suit. No matter on what approach they may use, the importance of data modeling in the database application development cannot be refused.